GAYA KEPEMIMPINAN TRANSFORMASIONAL KEPALA SEKOLAH DASAR DAN KEPUASAN KERJA GURU - Suyanto Suyanto; M Lies Endarwati; Ali Muhson (Universitas Negeri Yogyakarta, 2003)
Abstract The objectives of this research are to find out: (1) leadership style of elementary school principal (ESP) in Yogyakarta province; (2) the difference of leadership style between male and female of elementary school principal; (3) the differences of job satisfaction between male and female teacher; and (4) the correlation between woman’s of elementary school principal transformational leadership style and teacher’s job satisfaction based on gender perspective. Population of this research includes the entire elementary schoolteachers in Yogyakarta province. Multistage random sampling is used questionnaire, while technique data analysis is used descriptive analysis, t-test, and regression. The result of this research shows that most teachers said that their elementary school principal (ESP) has a high level of transformational leadership style; there is no different leadership style between male and female elementary school principal (t=1.22; p=0.225); most teachers have a high job satisfaction; there is no different job satisfaction between teacher who has a male and female elementary school principal (t=0.47; p=0.639); there is a positive correlation between transformational leadership style of elementary school principal and teacher’s job satisfaction (R=0.291 t=7.353, p=0.000). Regarding dender perspective, the result of this research shows that both male and female elementary school principal has a positive correlation between transformational leadership style and teacher’s job satisfaction. Keywords: elementary school principal, gender, teacher’s job satisfaction, and transformational style